2021
DOI: 10.1021/acs.energyfuels.1c02064
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ultrasmall NiCo2O4 Nanoparticle-Decorated N-Doped Graphene Nanosheets as an Effective Catalyst for Zn–Air Batteries

Abstract: Developing oxygen electrocatalysts with outstanding activity and low cost is vital to the promotion of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) of Zn–air batteries. Herein, an NiCo2O4 nanoparticle-decorated nitrogen-doped graphene nanosheet (NiCo2O4/N-G) is synthesized as a bifunctional electrocatalyst. The ultrasmall NiCo2O4 nanoparticle with an average particle size of 4 nm can introduce plentiful reaction active sites. Furthermore, the N-G nanosheets with small dimensions of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…It has been reported that the ORR electrocatalytic activity of Co-based catalysts is closely related to the abundance of Co 2+ because the exposure of Co 2+ active sites could promote the oxygen adsorption on catalysts surface and accelerate the electron transfer process . It was obviously noted that the Co 2+ cations were the predominant active species in the LaMnO 3 –CoO composite according to the fitting XPS spectra . Therefore, we can speculate that the composite containing more Co 2+ can present a higher electrocatalytic activity.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been reported that the ORR electrocatalytic activity of Co-based catalysts is closely related to the abundance of Co 2+ because the exposure of Co 2+ active sites could promote the oxygen adsorption on catalysts surface and accelerate the electron transfer process . It was obviously noted that the Co 2+ cations were the predominant active species in the LaMnO 3 –CoO composite according to the fitting XPS spectra . Therefore, we can speculate that the composite containing more Co 2+ can present a higher electrocatalytic activity.…”
Section: Resultsmentioning
confidence: 87%
“…31 It was obviously noted that the Co 2+ cations were the predominant active species in the LaMnO 3 −CoO composite according to the fitting XPS spectra. 32 Therefore, we can speculate that the composite containing more Co 2+ can present a higher electrocatalytic activity. In Figure 2d, three oxygen counterparts were located at 529.5, 531.3, and 533.3 eV, which were attributed to the lattice oxygen (O latt ), surface absorbed oxygen (O ads ), and oxygen-containing groups (O w ), respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Py-NHCP-1000 displays a stable potential platform of 1.49 V, and it is close to Pt/C (1.50 V). In addition, the peak power density of Py-NHCP-1000 is up to 165 mW cm –2 according to the polarization plots revealed in Figure c, which considerably precedes that of the Pt/C catalyst (127 mW cm –2 ) as well as those of most of the non-noble metal catalysts reported recently, signifying its possible application potential for energy conversion. From the galvanostatic discharge curves shown in Figure d, an ignorable voltage drop is observed after 36 h, which reveals a high stability of ZAB with the Py-NHCP-1000 catalyst.…”
Section: Results and Discussionmentioning
confidence: 56%
“…These data are fit to a line, the slope of which is the geometric C dl . The oxygen reduction reaction (ORR) activity at different temperatures was tested using the linear sweep voltammetry method . 4 mg of commercial Pt/C, 2 mg of XC-72 carbon, and 20 μL of Nafion solution (5 wt %) were dispersed into 380 μL of isopropanol and then sonicated for 30 min to form a homogeneous ink.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The oxygen reduction reaction (ORR) activity at different temperatures was tested using the linear sweep voltammetry method. 31…”
Section: Physicochemical and Electrochemical Characterizationmentioning
confidence: 99%